Development of BrailleBunny: a device to enhance braille learning. - Hoskin, Elizabeth R.; Pinder, Shane D.; Davies, T. Claire (Disability & Rehabilitation: Assistive Technology, 2024)
Braille use has been linked to higher rates of employment, education, financial self-sufficiency, and self-esteem. One area of the world particularly impacted by braille illiteracy is the Philippines. In 2016, Digital Learning for Development and All Children Reading released a "Grand Challenge for Development" that challenged researchers to address the need for assistive technologies to help children with sensory disabilities learn to read in the Philippines. The purpose of this research was to identify technical specifications, and then co-design and test a device that could be used both in developed and developing countries, specifically Canada and the Philippines. An iterative, co-design process was undertaken to develop a prototypical device, BrailleBunny. The extent to which the device fulfilled the design criteria and directions for future development were determined through a series of case studies with 25 end-users. The prototypical device requires improvement in financial accessibility, durability and reliability. All other criteria were met. Despite identified areas for improvement, the user feedback was positive, with the majority of users identifying that this device could provide transferrable learning to standard-size braille. With improvements, BrailleBunny, could be a valuable tool to increase the uptake of learning braille in the Philippines. An inexpensive device, BrailleBunny was developed to promote transferable braille literacy skills including writing with a slate and stylus for children learning to read. The BrailleBunny provides real-time auditory and tactile feedback, and functions in either English or Tagalog (the languages which are taught in the Filipino curriculum). Feedback from 25 children and adults indicated the potential for use within schools in both Canada and the Philippines.